From Formal Cooperation to Governance Practice: Lessons from Jakarta-Moscow Sister City Diplomacy in Urban Transport Reform (2017-2022) - Zahra Nathania, Vania; Muhamad Fathun, Laode (Jurnal Hubungan Internasional, 2026)
This paper investigates the dynamics of transposing formal diplomatic agreements into urban governance action within a specific timeframe, employing trade relations and exchanges through Jakarta–Moscow sister city cooperation (2017–2022) as an illustrative case study, with particular reference to Jakarta’s urban transport sector. Instead of seeing paradiplomacy as largely a symbolic vehicle for engagement, the article frames city diplomacy as an ongoing form of institutional embedding, thereby revealing how particular cooperative frameworks may be constitutive of policy processes and administrative coordination. Through qualitative analysis, the research investigated the manner in which diplomatic commitments were integrated into Jakarta’s transport governance arrangements. Results revealed how this joint effort allowed for structured technocratic exchanges, improved inter-agency coordination, and facilitated gradual innovations in digital traffic management as well as intermodal integration. While the cooperation did not lead to any radical restructuring of institutions, it passed beyond the realm of ceremonial diplomacy into one that made adaptations for governance in practice. The Jakarta–Moscow case suggests that sustained city diplomacy can operate as a mechanism of policy learning, allowing external knowledge to be gradually integrated into existing administrative systems. In this regard, formal subnational cooperation may evolve into governance practice through institutional alignment and gradual reform.